2008
DOI: 10.1007/s10546-008-9312-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Heterogeneity on the Temperature–Humidity Correlation and the Relative Transport Efficiency

Abstract: We derive a conceptual model of the flow over heterogeneous terrain consisting of patches with contrasting Bowen ratios. Upward moving eddies are assumed to carry heterogeneous properties, whereas downward moving eddies carry homogeneous properties. This results in a decorrelation of temperature and humidity as the contrast between the patches increases. We show that this model is able to reproduce the relationship developed by Lamaud and Irvine (Boundary-Layer Meteorol. 120:87-109, 2006). Some details differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
3
25
0
Order By: Relevance
“…4). In comparison, our data better fit the predictions of the conceptual model of Moene and Schüttemeyer (2008), taking into account the vegetative heterogeneity (as a characteristic of our experiment site).…”
Section: Behaviour Of λ θQ and The Latent Heat Flux Estimationsupporting
confidence: 76%
See 2 more Smart Citations
“…4). In comparison, our data better fit the predictions of the conceptual model of Moene and Schüttemeyer (2008), taking into account the vegetative heterogeneity (as a characteristic of our experiment site).…”
Section: Behaviour Of λ θQ and The Latent Heat Flux Estimationsupporting
confidence: 76%
“…Thus, the K − β relationship is likely to vary from site to site and needs local determination (cf. Moene and Schüttemeyer 2008). Likewise, the M − α relationship has to be further examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contrast between patches of hot, dry impervious areas and cool, wet vegetation may be reduced by altogether wetter surfaces in 2012, which is thought to increase correlation between temperature and humidity (Lamaud and Irvine, 2006;Moene and Schüttemeyer, 2008;Ramamurthy and Bou-Zeid, 2014). On the other hand, Lüdi et al (2005) found lower r T q coincides with lower β.…”
Section: Temperature-humidity Correlationmentioning
confidence: 98%
“…Even then, it should be noted that the entrainment ratio and thus the importance of greater heights may vary between scalars (Moene et al 2006b). In comparatively dry conditions, the heterogeneity of the latent heat flux at the surface is larger than that of the sensible heat flux (Moene and Schüttemeyer 2008), adding further uncertainty and changing the local entrainment ratio even if the absolute entrainment flux is constant.…”
Section: Possible Extensions To Passive Scalarsmentioning
confidence: 99%